2019
DOI: 10.3892/ijmm.2019.4451
|View full text |Cite
|
Sign up to set email alerts
|

Non‑toxic sulfur enhances growth hormone signaling through the JAK2/STAT5b/IGF‑1 pathway in C2C12 cells

Abstract: Insulin-like growth factor-1 (IGF-1) regulates cell growth, glucose uptake and protein metabolism, and is required for growth hormone (GH) signaling-mediated insulin production and secretion. IGF1 expression is associated with STAT5, which binds to a region (TTcNNNGAA) of the gene. Although sulfur is used in various fields, the toxicity of this element is a significant disadvantage as it causes indigestion, vomiting, diarrhea, pain and migraine. Therefore, it is difficult to conduct in vitro experiments to dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
(36 reference statements)
1
5
0
Order By: Relevance
“…NTS is a form of non-toxic mineral sulfur. Studies have shown the ability of NTS to enhance growth hormone signaling via the JAK2/STAT5b/IGF-1 axis and to produce anti-inflammatory effects against hyperglycemia in human monocytes [22,35]. MSM is another sulfur-containing natural compound with…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NTS is a form of non-toxic mineral sulfur. Studies have shown the ability of NTS to enhance growth hormone signaling via the JAK2/STAT5b/IGF-1 axis and to produce anti-inflammatory effects against hyperglycemia in human monocytes [22,35]. MSM is another sulfur-containing natural compound with…”
Section: Discussionmentioning
confidence: 99%
“…NTS is a form of non-toxic mineral sulfur. Studies have shown the ability of NTS to enhance growth hormone signaling via the JAK2/STAT5b/IGF-1 axis and to produce anti-inflammatory effects against hyperglycemia in human monocytes [ 22 , 35 ]. MSM is another sulfur-containing natural compound with various anti-inflammatory activities [ 38 ] and exercise-induced stress in racing horse muscle cells via p53-mediated SDHA/HPRT1 expression [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that repeated oral administration of NTS in rats did not induce cell death ( 23 , 24 ). In addition, it has been demonstrated that NTS can enhance growth hormone signaling by regulating the JAK2/STAT5b/IGF-1 axis ( 25 ). The present study hypothesized that NTS exhibits anti-inflammatory activity against LPS-induced inflammation by regulating JAK2/STAT3/IL-6 signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Many countries, including the USA, use a non-toxic form of dietary sulfur or natural sulfur for the treatment of many diseases, including inflammatory diseases [31]. A recent study demonstrated that non-toxic sulfur (NTS) extracted and processed from mineral sulfur enhances growth hormone signaling in mouse muscle cells [32]. Methylsulfonylmethane (MSM) is also a natural organic sulfur-containing compound present in food and beverages [33].…”
Section: Introductionmentioning
confidence: 99%